Editorial: Challenges, specificities and commonalities of transport research and policy within the BENELUX countries – the case of Luxembourg - Caruso, Geoffrey; Gerber, Philippe; Hesse, Markus; Viti, Francesco (European Journal of Transport and Infrastructure Research, 2015)
The papers included in this special issue of the EJTIR evolved from discussions and presentations given at the 2013 Transport Research Day of BIVEC, the ‘Benelux Interuniversity Association of Transport Researchers’, which took place at the University of Luxembourg in May 2013. This biannual event is organized in order to foster scientific exchange on related issues and offers a platform for early career researchers, most importantly PhD candidates, to present their work and receive scientific feedback. Different from the topic-wise rationale that is usually behind most other academic associations, submissions have to come from universities or representatives of the three Benelux countries: Belgium, the Netherlands and Luxembourg.